Female Athlete Triad/Relative Energy Deficiency in sport: A perspective interview with Professor Barbara Drinkwater - Carter, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Barbara Drinkwater has been a lifelong champion of equality for women in many areas of life well before it was widely accepted. Her "walking the walk" of women breaking barriers in traditional male roles in administration and leadership is exemplified by her election as the first woman president of the American College of Sports Medicine in 1988. Some of the controversial areas in which Barbara was vocal in the arena of women in sport, besides triad/relative energy deficiency in sport, include increased opportunity and participation, total equality, acceptance of diversity, intolerance of harassment and abuse, and fairness with transgender athletes. She co-founded the evidence-based advocacy group on the international stage known as Women Sport International. As a physiologist, Barbara has had a major influence on attention to the health of the female athlete, and she produced the original pioneering work in the field. Her impactful study, "Bone mineral density after resumption of menses in amenorrheic athletes," was published in the Journal of the American Medical Association in 1986. Since that time, the female athlete triad has set the stage for research and treatment to enhance women in physical activity at all levels.